2010
DOI: 10.1292/jvms.09-0318
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1A-Dependent Activities in Deer, Cattle and Horses

Abstract: ABSTRACT. The objective of this study was to investigate and characterize the metabolic activities of CYP1A in deer, cattle and horses in comparison to those of rats using ethoxyresorufin O-deethylation (EROD) and methoxyresorufin O-demethylation (MROD) assays. We performed an inhibition study for these activities using anti-rat CYP1A1 antibody and identified that these activities were due to the CYP1A subfamily. Interspecies differences in the CYP1A-dependent activities were highly observed in this study. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
(29 reference statements)
3
21
0
Order By: Relevance
“…CYP1A1 is primarily an extra-hepatic enzyme, as its hepatic expression is reported to be very low in rats and humans (Hadley, 1982; Ling et al, 2004; Martignoni et al, 2006; Schweikl et al, 1993; Voigt et al, 1993). However, our results demonstrating the expression of CYP1A1 in bovine liver are in agreement with previous reports where CYP1A1 has been shown to be highly expressed in the hepatic tissues in cows (Darwish et al, 2010 (a); Sivapathasundaram et al, 2001). CYP1A is also the most inducible CYP subfamily, and many chemicals present in dietary plant components, in addition to environmental pollutants like polycyclic aromatic hydrocarbons have been reported to enhance its expression (Ioannides, 1999; Ling et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…CYP1A1 is primarily an extra-hepatic enzyme, as its hepatic expression is reported to be very low in rats and humans (Hadley, 1982; Ling et al, 2004; Martignoni et al, 2006; Schweikl et al, 1993; Voigt et al, 1993). However, our results demonstrating the expression of CYP1A1 in bovine liver are in agreement with previous reports where CYP1A1 has been shown to be highly expressed in the hepatic tissues in cows (Darwish et al, 2010 (a); Sivapathasundaram et al, 2001). CYP1A is also the most inducible CYP subfamily, and many chemicals present in dietary plant components, in addition to environmental pollutants like polycyclic aromatic hydrocarbons have been reported to enhance its expression (Ioannides, 1999; Ling et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…The use of bovine tissues for studying the enzymatic activity in various organs, such as the liver, lungs, intestinal mucosa, kidneys, coronary arteries, and tongue, has become increasingly popular in recent years (Darwish et al, 2010(a), (b); Maté et al, 2015; Virkel et al, 2010; Zancanella et al, 2010). The proteolytic capacity of the bovine nasal mucosa has been used to investigate peptide transport and metabolism across the nasal mucosa (Lang et al, 1998, 1996; Schmidt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported the unique expression pattern of CYP1A1, in particular in ungulates. The high expression and the distribution of CYP1A1 mRNA in the tongue are markedly different from the CYP distribution pattern in rats or other laboratory animals (Darwish et al, 2010a and2010b). These results led us to investigate the distribution of CYP and xenobiotic-metabolizing enzymes (XMEs) in ungulates.…”
Section: Introductionmentioning
confidence: 99%
“…An additional limitation to the reproducible use of cell cultures for nasal transport studies is the lack of an immortalized nasal cell line that simulates the nasal epithelial and submucosal tissue interactions. The use of bovine tissues for studying the enzymatic activity of various organs like the liver, lungs, intestinal mucosa, kidneys, coronary arteries and tongue has become increasingly popular in recent years . This species has also been shown to be well‐suited for investigations of nasal permeation and metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…The use of bovine tissues for studying the enzymatic activity of various organs like the liver, lungs, intestinal mucosa, kidneys, coronary arteries and tongue has become increasingly popular in recent years. [24][25][26][27] This species has also been shown to be well-suited for investigations of nasal permeation and metabolism. [28] Using real-time reverse-transcriptase polymerase chain reaction (RT-PCR) and enzyme immunohistochemistry, we have previously demonstrated that CYP450 isoforms and corresponding proteins are expressed in the bovine nasal mucosa, and the enzymes are localized both in the epithelial as well as submucosal regions.…”
Section: Introductionmentioning
confidence: 99%